The Scandal of White Complicity in US Hyper-incarceration - Mikulich, A. author. aut Link
XVI, 203 p.
Keywords: The Scandal of White Complicity and U.S. Hyper-incarceration is a groundbreaking exploration of the moral role of white people in the disproportionate incarceration of African-Americans and Latinos in the United States. Alex Mikulich, Laurie Cassidy, and Margaret Pfeil are white Catholic theologians developing understanding of how whiteness operates in the U.S. system of incarceration and witnessing to a Christian nonviolent way for whites to subvert our oppression of brothers and sisters of color.